Special Issue: Post-Keynesian and Institutional political economy. Editorial to the Special Issue - Marc Lavoie; Mario Seccareccia (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
In May 2011, the editors of Intervention: European Journal of Economics and Economic Policies, which is now named the European Journal of Economics and Economic Policies: Intervention (EJEEP), decided to put together a special issue on post-Keynesian and Institutional Economics.
Keywords: E0; 330; Special Issue